Tindak Tutur Ilokusi dalam Film “Anak Karaeng” Karya Amin D.B: Illocutionary Speech Acts in the Film "Anak Karaeng" by Amin D.B - Al-Alim, St. Nur Alifiyah; Agussalim AJ, Andi; Asia M, Asia M (Journal Studies in Indonesian Language and Literature, 2025)
This study analyzes illocutionary speech acts in the film "Anak Karaeng" by Amin D.B., focusing on how the dialogues reflect and preserve Makassar cultural values, especially the kekaraengang customs. The research method involves direct observation of the film and literature review on pragmatics and Makassar culture, with data analyzed through reduction, presentation, and triangulation for validation. Results show five types of illocutionary acts: directive, expressive, commissive, representative, and declarative, dominated by directive and expressive acts that enrich the storyline and character interactions while reflecting cultural values and social dynamics of Makassar society. The study highlights the film’s role as a medium for cultural preservation and differs from others by using the Makassar regional language, offering deep insights into the role of language in strengthening kekaraengang traditions and local cultural identity.